Theses and concepts of Newton da Costa - Santos, Katia Cilene da Silva (Argumentos - Revista de Filosofia, 2023)
In this text, we explore some of the most important theses developed by Newton da Costa throughout his philosophical career. We present concepts and ideas from his works, gathering contributions in the fields of logic and philosophy of science. The focus will be on works Sistemas formais inconsistentes, Ensaios sobre os fundamentos da lógica and O conhecimento científico, of which we will explain the themes and some of the concepts and results achieved by the philosopher. The purpose of this presentation is to highlight the originality of his thought, that is, how his personal answers address relevant questions of the history of philosophy, mathematics and logic.